Exit and Save : Migration and Saving under Violence - Grun, Rebekka E. (2012)
This paper examines how households trade off migration and savings when subject to exogenous violence. The authors propose that households under violence decide jointly on migration and saving, because a higher asset-stock is more difficult to carry to a new place. When confronted with exogenous violence, households are expected to consider migration, and reduce their assets, both in order to reduce their exposure to violence, and to make migration easier. In some cases, after a migration decision has been taken, savings can increase as a function of violence to ensure a minimum bundle to carry. Empirical evidence from rich Colombian micro-data supports the conceptual framework for violence that carries a displacement threat, such as guerrilla attacks.